Magnetocaloric Effect in Iron-Phosphide Based Phases - He, Allan (My University, 2017)
Ever since the discovery of the giant magnetocaloric effect (GMCE) in the Gd5(Si,Ge)4 phases, magnetic cooling has gained significant interest because of its potential environmental benefits and increased efficiency compared to vapour-based refrigeration. This current work is focused on one of the most promising GMCE systems, the (Mn,Fe)2(Si,P) materials. An alternative synthetic route has been explored for the Mn2-xFexSi0.5P0.5 and MnFeSiyP1-y series which is capable of producing phase-pure samples. The new preparation technique eliminates common impurities that arise from established methods thus providing a more accurate description of the structural and physical properties. The low cost, non-toxicity, abundance of starting materials and easy tuning of the magnetic properties make these materials desirable for potential applications. Phase-pure magnetocaloric Mn2-xFexSi0.5P0.5 materials (x = 0.6, 0.7, 0.8, 0.9) were synthesized through arc-melting followed by high temperature sintering. Structural features of samples with x = 0.6, 0.9 were studied through temperature dependent synchrotron powder x-ray diffraction. Magnetic measurements established the Curie temperature, thermal hysteresis, and magnetic entropy change of this system. According to the diffraction and magnetization data, all of the samples were shown to have a first-order magnetostructural transition which becomes less pronounced for Mn-richer samples. The MnFeSixP1-x phases (x = 0.30, 0.35, 0.40, 0.48, 0.52, 0.54, 0.56) have also been synthesized by the same method. For the first time, single crystals of x = 0.30, 0.40 were successfully grown. Variable temperature x-ray diffraction experiments for x = 0.30 were completed which show the structural changes across the phase transition. This structural data was complemented with magnetization data providing Curie temperatures and thermal hysteresis.
Keywords: Magnetocaloric effect; Fe2P; Iron Phosphide; Entropy change; MCE; magnetization; magnetic cooling; (Mn,Fe)2(Si,P); x-ray diffraction; arrot plot; arc melting; sintering